Implementation of Transformational Leadership for Improving Teacher Performance in Secondary Schools - Karjuni , Agus (International Journal of Sharia Business Management, 2024)
This study aims to analyze the application of transformational leadership in improving teacher performance in secondary schools. Transformational leadership is considered as a leadership model that is able to drive positive change by fostering motivation, commitment, and higher performance among teachers. The research method used is a quantitative approach with a survey design. Data were collected through questionnaires distributed to teachers in several secondary schools, which were then analyzed using descriptive statistical techniques and linear regression. The results of the study indicate that there is a positive and significant relationship between the application of transformational leadership and improved teacher performance. Aspects of transformational leadership such as inspiration, motivation, intellectual stimulation, and individual attention significantly contribute to improving teacher performance, both in terms of teaching effectiveness, collaboration with colleagues, and innovation in the learning process. The conclusion of this study is that the application of transformational leadership in secondary schools can significantly improve teacher performance. Therefore, schools are advised to develop leadership programs that focus on transformational principles in order to improve the overall quality of education